Héctor Raúl Sandler G. Alquileres e inflación. México : Ed. JUS, 1977. 244 P. - Pírez, Pedro (Estudios Demográficos y Urbanos, 1977)
HÉCTOR RAÚL SANDLER G., Alquileres e inflación, México, Ed. JUS, 1977.